Kajian Tekno-Ekonomi Penerapan Insinerator Waste-to-Energy di Indonesia (Kasus pada Kota “X"): A Techno-Economic Study on the Application of Waste-to-Energy Incinerator in Indonesia (Case on City “X”) - Manis Yuliani; Geby Otivriyanti; Naufal Riadhi Yusuf; Ayudia Mutiara Fani; Wahyu Purwanta (Jurnal Teknologi Lingkungan, 2022)
In order to realize net zero emissions in waste sector, the government encourages the application of Waste-to-Energy (WtE) thermal process technology in 12 cities in Indonesia. There are many obstacles and challenges in implementing WtE as an alternative for waste management, starting from changes in consistency of regulations, environmental issues as well as technical and economic feasibility. Therefore, this study aims to examine the Techno-Economics of WtE Incinerator Implementation in Indonesia by taking the case in City "X" as an illustration for stakeholders in making decisions. The methods used include the desk study, direct observation, and interviews. In this study, City "X" becomes a model for the implementation of WtE with a waste processing capacity of 1,500 tpd which is a typical waste generation in big cities in Indonesia. City set a target to reduce 80–90% of waste volume. After technology selection stage, the MGI was selected as the main WtE unit. The plant is designed with a capacity of 1,500 tons/day of waste with a calorific value of 6,276 kJ/kg, 26% plant efficiency, 8,000 hours/year operation so that it will produce 28.33 MW of electricity or energy equivalent to 226,633 MWh/year. This electrical power will be used for internal purposes by 15% so that the total net electricity for the PLN grid is 24.08 MW. This WtE has a capital expenditure (Capex) of 2.2 billion IDR/ton/day and operational expenditure (Opex) 167 million IDR /year/ton per day with an estimated construction in 2025. The electricity price obtained from this capacity is 1,819 IDR/kWh. Based on the estimated value of the cost of capital, the selling price of electricity and the assumption that the loan will be returned for 10 years with  interest rate of 6%, the WtE project gets a tipping fee of 642,779 IDR/ton of waste. Keywords: Waste-to-energy, Municipal waste, Techno economy ABSTRAK Dalam mewujudkan net zero emission di sektor persampahan, pemerintah mendorong penerapan teknologi Waste-to-Energy (WtE) di 12 Kota. Banyak kendala dan tantangan dalam penerapan WtE, mulai dari konsistensi regulasi, isu lingkungan, hingga kelayakan teknis dan ekonomi. Oleh karena itu, penelitian ini bertujuan untuk mengkaji tekno-ekonomi penerapan insinerator WtE di Indonesia dengan mengambil kasus di Kota “X” sebagai gambaran bagi stakeholders untuk mengambil keputusan. Metode yang digunakan meliputi metode desk study, pengamatan langsung, dan wawancara. Dalam penelitian ini Kota “X” menjadi model penerapan WtE kapasitas 1.500 ton/hari yang merupakan tipikal kapasitas yang umum di kota di Indonesia.  Kota “X” menetapkan target pengolahan sampah mereduksi 80–90% dari volume sampah. Setelah melalui seleksi teknologi maka dipilih Moving Grate Incinerator sebagai unit utama WtE. Plant dirancang berkapasitas 1.500 ton/hari sampah dengan nilai kalor 6.276 kJ/kg, efisiensi termal 26%, operasi 8.000 jam/tahun sehingga akan menghasilkan energi listrik 28,33 MW atau energi setara 226.633 MWh/tahun. Daya listrik ini akan digunakan keperluan internal sebesar 15% sehingga total listrik bersih untuk ke jaringan PLN sebanyak 24,08 MW. WtE ini memiliki Capex Rp2,2 miliar/ton/hari serta Opex Rp167 juta/tahun/ton per hari dengan perkiraan dibangun tahun 2025 dan harga listrik yang diperoleh adalah Rp1.819/kWh. Berdasarkan perkiraan besaran nilai biaya modal, harga penjualan listrik dan asumsi bahwa pinjaman akan dikembalikan selama 10 tahun dengan bunga bank sebesar 6%, maka proyek WtE ini mendapatkan nilai tipping fee sebesar Rp642.779/ton sampah. Kata kunci: Waste-to-energy, Sampah perkotaan, Tekno ekonomi